Cold Acclimation Improves the Desiccation Stress Resilience of Polar Strains of Klebsormidium (Streptophyta) - Rippin, Martin; Borchhardt, Nadine; Karsten, Ulf; Becker, Burkhard (Frontiers in Microbiology, 2019)
Biological soil crusts (BSCs) are complex communities of autotrophic, heterotrophic, and saprotrophic (micro)organisms. In the polar regions, these biocrust communities have essential ecological functions such as primary production, nitrogen fixation, and ecosystem engineering while coping with extreme environmental conditions (temperature, desiccation, and irradiation). The microalga Klebsormidium is commonly found in BSCs all across the globe. The ecophysiological resilience of various Klebsormidium species to desiccation and other stresses has been studied intensively. Here we present the results of transcriptomic analyses of two different Klebsormidium species, K. dissectum and K. flaccidum, isolated from Antarctic and Arctic BSCs. We performed desiccation stress experiments at two different temperatures mimicking fluctuations associated with global change. Cultures grown on agar plates were desiccated on membrane filters at 10% relative air humidity until the photosynthetic activity as reflected in the effective quantum yield of photosystem II [Y(II)] ceased. For both species, the response to dehydration was much faster at the higher temperature. At the transcriptome level both species responded more strongly to the desiccation stress at the higher temperature suggesting that adaptation to cold conditions enhanced the resilience of both algae to desiccation stress. Interestingly, the two different species responded differently to the applied desiccation stress with respect to the number as well as function of genes showing differential gene expression. The portion of differentially expressed genes shared between both taxa was surprisingly low indicating that both Klebsormidium species adapted independently to the harsh conditions of Antarctica and the Arctic, respectively. Overall, our results indicate that environmental acclimation has a great impact on gene expression and the response to desiccation stress in Klebsormidium.